PURITANISM VIS-A-VIS TRADITIONALISM: ISLAM IN MODERN INDONESIA - Endang Turmudi (Research and Development Center for Guidance for Religious Societies and Religious Services, the Research and Development and Education and Training Agency of the Ministry of Religious Affairs of the Republic of Indonesia (MORA), 2012)
Islamic movement in Indonesia that become stronger during political reformation in the end of 1990s, has been spread to every segment of society. It has created new religious school students who practice religious dogma. Out of the reality, it gives positive effect toward society’s faith. This movement has made new Islam face which differs from the old ones. The strong effect of various inmternational organisations in this country which bring Islamism, has created new puritan and intolerant to various differences in the society. The Wahhabism that is carried by various salafi in this movement trigger various conflicts among Indonesian moslems. It is because this movement has made the pristine Islam and make many reactions the tradisionalists who accommodative and as majority Indonesia moslems. The new movements has in fact, invited and strengthened traditionalism. In other words, the born of modern Islamism movement has caused developing Islam with puritan fundamental characteristic face to face with traditionalism as Indonesian Islam mainstream.